Are Male and Female Students Different in High-Order Thinking Skills? - Dewi Endah Sari; Iin Hindun; Nurul Mahmudati; Fuad Jaya Miharja; Ahmad Fauzi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
High-order thinking skills (HOTS) are competencies that must be possessed by male and female students in 21st Century era. The purpose of this quasi-experimental pretest-posttest design was to determine the effect of gender on the level of HOTS empowerment of high school students. The subjects of this study were students of SMA Negeri 1 Malang and the sample of the study was students of class XI MIPA 10. All students receive biology learning by applying Problem-based Learning (PBL) combined with Two Stay-Two Stray (TSTS) assisted by “Sangkar Hati” media. The collected data were analyzed by using one way ANCOVA. Based on the results of data analysis, it can be concluded that HOTS achievement of female students is not significantly different from male students. Through the findings of this study, it is expected that the implementation of Biology learning in other schools will also implement innovative education with creative media that can empower HOTS of female and male students.